2008
DOI: 10.1097/ypg.0b013e3283118468
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 9: linkage for borderline personality disorder features

Abstract: Objective A large-scale twin study implicated genetic influences on borderline personality disorder (BPD) features, with a heritability estimate of 42%. To date, no genome-wide linkage study has been conducted to identify the genomic region(s) containing the quantitative trait loci that influence the manifestation of BPD features.Methods We conducted a family-based linkage study using Merlin regress. The participating families were drawn from the community-based Netherlands Twin Register. The sample consisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 31 publications
1
23
1
Order By: Relevance
“…Multivariate modeling indicates that there is likely to be a single common genetic factor reflecting vulnerability to PD pathology and/or negative emotionality, and two other genetic factors reflecting high impulsivity/low agreeableness and introversion [13]. A genome-wide linkage study found chromosome 9 to be the most likely candidate for genes influencing BPD [16], but no specific genes have been identified.…”
Section: Findings From Genetic Studiesmentioning
confidence: 97%
“…Multivariate modeling indicates that there is likely to be a single common genetic factor reflecting vulnerability to PD pathology and/or negative emotionality, and two other genetic factors reflecting high impulsivity/low agreeableness and introversion [13]. A genome-wide linkage study found chromosome 9 to be the most likely candidate for genes influencing BPD [16], but no specific genes have been identified.…”
Section: Findings From Genetic Studiesmentioning
confidence: 97%
“…Although happiness is often seen as the counterpart of depression, the regions with suggestive linkage for happiness have not been reported for depression so far (e.g., Middeldorp et al, 2008). Furthermore the regions on chromosome 1 and 19 have also not been suggested in a linkage scan for borderline personality disorder features (Distel et al 2008) and a linkage scan for Neuroticism (Wray et al, 2008). A next step would be to run a genome wide association analyses for happiness.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent twin study indicated that an underlying latent trait of borderline pathology was about 51% heritable and 49% due to unique environmental effects (Distel et al, 2010; see also Distel et al, 2011;Distel, Hottenga, Trull, & Boomsma, 2008). It is assumed that particular heritable traits, such as impulsivity and affect instability, contribute to BPD phenomena, but it is not yet clear what other trait markers may be relevant (Paris, 2009).…”
mentioning
confidence: 95%